2018
DOI: 10.1016/j.neuron.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Blocking NMDAR Disrupts Spike Timing and Decouples Monkey Prefrontal Circuits: Implications for Activity-Dependent Disconnection in Schizophrenia

Abstract: SUMMARY We employed multi-electrode array recording to evaluate the influence of NMDA receptors (NMDAR) on spike-timing dynamics in prefrontal networks of monkeys as they performed a cognitive control task measuring specific deficits in schizophrenia. Systemic, periodic administration of an NMDAR antagonist (phencyclidine) reduced the prevalence and strength of synchronous (0-lag) spike correlation in simultaneously recorded neuron pairs. We employed transfer entropy analysis to measure effective connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 68 publications
(125 reference statements)
4
85
1
Order By: Relevance
“…For instance, in a working memory task, ketamine was found to increase spiking activity of response-selective cells, but decrease activity of the task-relevant delay-tuned cells in primate prefrontal cortex 26 . Such specificity might explain why several studies reported less conclusive effects of NMDA-R antagonists on overall prefrontal firing rates in monkeys 26,43 . In vitro work has also revealed the excitatory post-synaptic potentials (EPSPs) of prefrontal pyramidal neurons are much more reliant on NMDA-R conductance than parvalbumin interneurons 44 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a working memory task, ketamine was found to increase spiking activity of response-selective cells, but decrease activity of the task-relevant delay-tuned cells in primate prefrontal cortex 26 . Such specificity might explain why several studies reported less conclusive effects of NMDA-R antagonists on overall prefrontal firing rates in monkeys 26,43 . In vitro work has also revealed the excitatory post-synaptic potentials (EPSPs) of prefrontal pyramidal neurons are much more reliant on NMDA-R conductance than parvalbumin interneurons 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in synaptic plasticity expression may explain the hubs loss seen in schizophrenia. It has been suggested that spike timing-dependent plasticity alterations may be responsible of progressive disconnection of prefrontal circuits [175]. Altered NMDA-mediated synaptic plasticity reduces temporal correlation between converging inputs to connected neurons and could lead to additional activity-dependent disconnection of prefrontal networks [175].…”
Section: Synaptic Plasticity Dysfunction May Drive Brain Network Disrmentioning
confidence: 99%
“…It has been suggested that spike timing-dependent plasticity alterations may be responsible of progressive disconnection of prefrontal circuits [175]. Altered NMDA-mediated synaptic plasticity reduces temporal correlation between converging inputs to connected neurons and could lead to additional activity-dependent disconnection of prefrontal networks [175]. In fact, subverted spike timing-dependent plasticity could induce LTD instead of LTP in prefrontal networks, ultimately producing progressive disruption of anterior hubs and generating a persistent disconnection within the rich club.…”
Section: Synaptic Plasticity Dysfunction May Drive Brain Network Disrmentioning
confidence: 99%
“…To relate the computations required for forms of cognitive control that are disrupted in schizophrenia to the activity of individual neurons in prefrontal networks, our lab recently translated a variant of the AX continuous performance task (AX-CPT) known as the dot-pattern expectancy (DPX) task that measures deficits in patients to nonhuman primates (Blackman et al, 2013(Blackman et al, , 2016Zick et al, 2018). In the current study we use linear electrode arrays to record MD and PFC neural activity simultaneously during DPX task performance.…”
Section: Introductionmentioning
confidence: 99%